Role of Serial Transverse Enteroplasty in the Management of Adult-Type Short Bowel Syndrome: Experience from a Single Tertiary Referral Hospital in Turkey - Yaprak, Muhittin; Doğru, Volkan; Erdoğan, Okan (Turkish Journal of Gastroenterology, 2021)
Background: There is little knowledge with regard to the management of intestinal failure in countries where home care services and dedicated intestinal rehabilitation centers are limited. This study presents a single-center experience of treating adult-type short bowel syndrome (SBS) with serial transverse enteroplasty (STEP).Methods: Medical records were retrospectively reviewed from November 2009 to April 2018 on patients with adult-type SBS. All patients underwent STEP, and a representative quota sample of control patients treated with conventional measures were included. Clinico-demographic characteristics including baseline and post-treatment information about the orientation of bowel alignment and nutritional status were evaluated.Results: The mean patient age was 51.1 ± 16.2 in the STEP group and 57.6 ± 12.7 in the control group (P = .304). The median small bowel length was 60 cm (interquartile range (IQR): 40-90) in the STEP group (before the lengthening) and 90 cm (IQR: 70-100) in the control (at the initiation of intestinal rehabilitation) (P = .035). Durations of median follow-up were 18 months (IQR: 14-58) and 10 months (IQR: 3-14), respectively (P = .019). In the STEP group, the mean increase in bowel length after STEP was 37.3 ± 11.6 cm, and at their follow-up 7 patients (64%) had successfully progressed to enteral autonomy. In the control group, only 3 patients (27%) were successful. Mean time to wean parenteral nutrition was 45 ± 54 days, and the mean increase in enteral calorie intake was 1.79 ± 1.60-fold after lengthening in the STEP group.Conclusions: STEP is an easy-to-perform procedure in the surgical rehabilitation of adult-type SBS. When performed simultaneously with reconnection surgery, it may offer a cost-effective and comprehensive solution to the treatment strategy in middle income settings.